Efektivitas Media Canva dalam Pembelajaran IPAS pada Materi Rantai Makanan - Septri Larissa; Elfia Sukma; Inggria Kharisma (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The problem underlying this study is that IPAS instruction remains unengaging and difficult for students to understand due to the limited use of interactive learning media, particularly for abstract concepts such as food chains. This study aims to analyze the effectiveness of using Canva as a learning medium in IPAS instruction on the topic of food chains in fifth-grade elementary school. This study employs a literature review method (library research) by examining various data sources obtained through Google Scholar, SINTA, and relevant national journals over the past ten years. Data collection was conducted through documentary studies, while data analysis utilized the Miles and Huberman interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the analysis indicate that the use of Canva can improve student learning outcomes, motivation, and understanding of food chain material through visual and interactive presentations. Additionally, the use of Canva supports the implementation of 21st-century learning through the integration of technology into the learning process. Therefore, Canva can be deemed effective in improving the quality of IPAS learning in elementary schools.